Neural Circuits Underlying Social Fear in Rodents: An Integrative Computational Model - Alfieri, Valerio; Mattera, Andrea; Baldassarre, Gianluca (Frontiers in Systems Neuroscience, 2022)
Social avoidance in rodents arises from a complex interplay between the prefrontal cortex and subcortical structures, such as the ventromedial hypothalamus and the dorsal periaqueductal gray matter. Experimental studies are revealing the contribution of these areas, but an integrative view and model of how they interact to produce adaptive behavior are still lacking. Here, we present a computational model of social avoidance, proposing a set of integrated hypotheses on the possible macro organization of the brain system underlying this phenomenon. The model is validated by accounting for several different empirical findings and produces predictions to be tested in future experiments.